2017
DOI: 10.1148/radiol.2017162403
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MR Imaging Signatures of Cognitive Impairment in Active Professional Fighters

Abstract: Purpose To investigate whether combining multiple magnetic resonance (MR) imaging modalities such as T1-weighted and diffusion-weighted MR imaging could reveal imaging biomarkers associated with cognition in active professional fighters. Materials and Methods Active professional fighters (n = 297; 24 women and 273 men) were recruited at one center. Sixty-two fighters (six women and 56 men) returned for a follow-up examination. Only men were included in the main analysis of the study. On the basis of computeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 46 publications
2
35
0
1
Order By: Relevance
“…In addition, paths involving cingulum, hippocampus, parahippocampus, amygdala, and thalamus showed a significantly lower WM connectivity in cognitively impaired fighters, and all these regions have been implicated to be involved in memory (Johns, ). Furthermore, in this same cohort, volumetric loss in thalamus and its association with neuropsychological outcomes (Bernick et al, ) has been indicated to predict cognitive decline (Mishra et al, ) due to RHI. These findings suggest that the RHI in fighters exhibiting cognitive decline had a significant WM connectivity damage in regions involving executive and working memory which may be responsible for their poor functional outcome.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, paths involving cingulum, hippocampus, parahippocampus, amygdala, and thalamus showed a significantly lower WM connectivity in cognitively impaired fighters, and all these regions have been implicated to be involved in memory (Johns, ). Furthermore, in this same cohort, volumetric loss in thalamus and its association with neuropsychological outcomes (Bernick et al, ) has been indicated to predict cognitive decline (Mishra et al, ) due to RHI. These findings suggest that the RHI in fighters exhibiting cognitive decline had a significant WM connectivity damage in regions involving executive and working memory which may be responsible for their poor functional outcome.…”
Section: Discussionmentioning
confidence: 83%
“…Finally, perfusion measures using arterial spin labeling (ASL) MRI has also shown significant deficits in the thalamus, cingulate gyri, cerebellum, cuneus, and temporal lobes (Eierud et al, ; Koerte et al, ; Mishra et al, ). Even multivariate MRI measures combining voxelwise volumetric, perfusion, and dMRI‐derived measures (Mishra et al, , ) have identified deficits in several brain regions that were correlated with exposure and neuropsychological scores in participants with RHI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both static and dynamic FC were used as features to classify cognitive impairment status of fighters. Classification framework included an automated feature selection step and a radial basis functional classifier step (see Mishra et al, 2017 , for details). A ten-fold cross-validation was used to determine the classification accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the neuropathological studies of CTE, in vivo research has begun to investigate the association between cumulative exposure to RHI and long-term neurobehavioral outcomes. Several case series and empirical studies show evidence of cognitive, behavioral, and mood disturbances, 5,10,[41][42][43] as well as structural, functional, and molecular brain alterations [44][45][46][47][48][49][50][51][52] in participants presumably at high risk of CTE (e.g., former NFL players, boxers). Roberts et al 43 conducted a survey study among 3,506 former professional American football players to examine the relationship between American football play and self-reported cognition-related quality of life and reported symptoms of depression and anxiety.…”
Section: In Vivo Evidencementioning
confidence: 99%